2016
DOI: 10.1080/03008207.2016.1177037
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic regulation of bone cells

Abstract: Bone is a major organ in the skeletal system that supports and protects muscle and other organs, facilitates movement and hematopoiesis, and forms a reservoir of minerals including calcium. The cells in the bone, such as osteoblasts, osteoclasts, and osteocytes, orchestrate sequential and balanced regulatory mechanisms to maintain bone and are capable of differentiating in bones. Bone development and remodeling require a precise regulation of gene expressions in bone cells, a process governed by epigenetic mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 157 publications
(145 reference statements)
1
22
0
1
Order By: Relevance
“…However, we observed that lycopene significantly repressed the expression level of DNMT3a but did not affect DNMT1 and DNMT3b. Previous studies have demonstrated that DNMT3a is a negative regulator of IRF8 [31]. Therefore, this result further indicates that lycopene treatment affecting the mRNA levels of IRF1 and IRF7 may only be caused by its role in IFNγ.…”
Section: Discussionsupporting
confidence: 57%
“…However, we observed that lycopene significantly repressed the expression level of DNMT3a but did not affect DNMT1 and DNMT3b. Previous studies have demonstrated that DNMT3a is a negative regulator of IRF8 [31]. Therefore, this result further indicates that lycopene treatment affecting the mRNA levels of IRF1 and IRF7 may only be caused by its role in IFNγ.…”
Section: Discussionsupporting
confidence: 57%
“…Chromatin condensation and histone acetylation are regulated by epigenetic modulators, such as type I HDACs. HDAC1, HDAC2, and HDAC3 have been implicated in playing a role in osteogenic differentiation of hMSCs ( 20 , 29 31 ). To investigate whether disruption of the KASH domain leads to altered activity and levels of HDAC enzymes, we analyzed mRNA expression of HDAC1, HDAC2, and HDAC3.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that epigenetic remodeling is important in precise regulation of gene expression of hMSCs in bone development and remodeling ( 13 , 18 , 19 ). It has been suggested that perturbation of epigenetic programs, leading to changes in histone acetylation landscapes and chromatin structure, can affect the function and activity of hMSCs and contributes to pathologies defined by bone loss (osteoporosis, osteoarthritis) ( 15 , 20 ). We previously demonstrated the role of mechanical cues in controlling hMSC epigenetic programming, linking persistent chromatin remodeling to mechanical memory induced by long-term culture on stiff hydrogel substrates ( 19 ).…”
mentioning
confidence: 99%
“…го Российской ассоциацией по остеопорозу как без, так и с учетом минеральной плотности кости (МПК) [1], созданного в соответствии с европейскими рекомендациями по диагностике и ведению больных с постменопаузальным остеопорозом [2]. Диагноз ОП ставился по критериям ВОЗ при проведении DXA.…”
Section: диагностические возможности различных методов выделения попуunclassified